1981
DOI: 10.1530/acta.0.0960252
|View full text |Cite
|
Sign up to set email alerts
|

Modification of pituitary-adrenal feedback sensitivity in young rats by neonatal treatment with cortisol

Abstract: Neonatal exposure of rats to cortisol acetate was found to alter pituitary-adrenal feedback regulation at 20\p=n-\25 days of age. Plasma levels of adrenocorticotrophin (ACTH) after ether stress were reduced in cortisol\x=req-\ treated rats pre-treated with 100 \g=m\g corticosterone/100 g body weight, while rats given vehicle neonatally did not show suppression of the ACTH response below levels in animals given saline only or not injected as pre-treatments. Neonatal cortisol increased sensitivity to dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Interestingly, high endogenous Cort levels induced by maternal deprivation did not appear to be detrimental for the adrenocortical response of adult rats to stress, contrary to the effects of exogenous administration of GCs on some adrenal parameters, such as adrenal relative weight (29). Several studies that examined the effects of neonatal administration of GCs show that 20-to 25-day-old pups present lower plasma ACTH levels in response to ether and increased feedback sensitivity in response to dexamethasone, without change of Cort-binding globulin binding capacity (7). When tested at 45-48 days of age, hydrocortisonetreated female rats show decreased plasma Cort response to novelty (mild stress) and to ether (intense stress), whereas reduced Cort levels in males is seen in response to novelty, but not ether.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, high endogenous Cort levels induced by maternal deprivation did not appear to be detrimental for the adrenocortical response of adult rats to stress, contrary to the effects of exogenous administration of GCs on some adrenal parameters, such as adrenal relative weight (29). Several studies that examined the effects of neonatal administration of GCs show that 20-to 25-day-old pups present lower plasma ACTH levels in response to ether and increased feedback sensitivity in response to dexamethasone, without change of Cort-binding globulin binding capacity (7). When tested at 45-48 days of age, hydrocortisonetreated female rats show decreased plasma Cort response to novelty (mild stress) and to ether (intense stress), whereas reduced Cort levels in males is seen in response to novelty, but not ether.…”
Section: Discussionmentioning
confidence: 88%
“…This explains why authors [10,11,29] found a decrease in response to ether at 23 days of life in control-treated rats be cause they compared the response to normal rats treated with ether and not to the basal levels in the former groups. Another author [21] did not find an increase in plasma corti costerone in cortisol-treated rats after ether; in all the above experiments, plasma cortico sterone was measured by bioassay or fluorometric micromethod and Sprague-Dawley rats were used.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while neonatal dexamethasone treatment also reduces brain GR in adulthood (10), it attenuates the HPA response to stress (11, 12). Similarly, administration of the endogenous GCs, cortisol or corticosterone, in the first week of postnatal life reduces both basal and stress‐induced HPA activity in adulthood (13, 14) and may, like dexamethasone (11), augment the sensitivity of the HPA axis to GC feedback (15, 16). A substantive literature shows that early life stress also exerts profound long‐term effects on HPA function (17).…”
mentioning
confidence: 99%